2014
DOI: 10.5539/ijef.v6n8p229
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Failures in Multiple-Currency Regime in Zimbabwe (2009–2012)

Abstract: Upsurge in bank failure cases under a more stable currency environment are rare, but the Zimbabwean case raised a lot of questions, which justified the need to deeply investigate sources of bank failures. This is considered an imperative move considering the impact that bank failures pose to stakeholders outside the banking sector such as investors and depositors, the Zimbabwean banking sector itself as well as the entire economy. This study investigated the determinants of bank failures in Zimbabwe under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, he opined there is a significant relationship between those collapse banks and their profit, total loans, return on capital and total capital. Alhassan et al [29] found in their study that the quality of the bank's assets was largely dependent on the performance of their loans with declining Non Performing Loans (NPLs), the size of the loans, and the market size, the exchange rate and GDP growth of that country. Haven reviewed much literature Alhassan et al [29] concluded that insufficient research on the determinant of banks' assets quality is done in developing countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he opined there is a significant relationship between those collapse banks and their profit, total loans, return on capital and total capital. Alhassan et al [29] found in their study that the quality of the bank's assets was largely dependent on the performance of their loans with declining Non Performing Loans (NPLs), the size of the loans, and the market size, the exchange rate and GDP growth of that country. Haven reviewed much literature Alhassan et al [29] concluded that insufficient research on the determinant of banks' assets quality is done in developing countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Alhassan et al, [29], focusing on specific components of banks in Ghana, consider the show to be diverse. The bank is protected by relevant variables to non-regulatory elements that come from the point of view of the workers' explanations for bank closures in Ghana.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Z=6.56 X1 + 3.26 X2 + 6.72 X3 + 1.05 X4 Regression and Error Correction Model Most established approaches are more appropriate to measure the bank soundness of the banking industry in developed rather than in developing countries [11]. Hence, the author chooses the aggregate research method tabulation that complements the Indonesian banking industry, referenced by Bank Indonesia [12] and Canicio and Blessing [22]. The variables used almost cover CAMELS indicators and exclude the variable measuring sensitivity to market risk.…”
Section: Data and Processing Analysis Altman Z-score Modificationmentioning
confidence: 99%
“…The author then applied regression analysis of micro-prudential and macroeconomics indicators, such as GDP, inflation, and exchange rate return, to evaluate the determinants. Combining Bank Indonesia's micro-prudential and macroeconomic indicators with references from Canicio and Blessing [22], the author indicates some observable variables to portray the determinants of bank stability in Indonesia seen in Table 3. Measures the effectiveness of the bank in utilizing its assets and liabilities.…”
Section: Stability Determinantsmentioning
confidence: 99%
See 1 more Smart Citation